2020
DOI: 10.3390/s20041051
|View full text |Cite
|
Sign up to set email alerts
|

An Unmanned Aerial Vehicle-Based Gas Sampling System for Analyzing CO2 and Atmospheric Particulate Matter in Laboratory

Abstract: We developed and tested an unmanned aerial vehicle-based gas sampling system (UGSS) for collecting gases and atmospheric particulate matter (PM). The system applies an alternative way of collecting both vertical and horizontal transects of trace gases in order to analyze them in the laboratory. To identify the best position of the UGSS intake port, aerodynamic flow simulations and experimental verifications of propeller airflow were conducted with an unmanned aerial vehicle (UAV) in hover mode. The UGSS will a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Such laboratory analysis depends on the use of large canisters and sorbent cartridge devices, which must be carried by a large drone. Li et al (2020) also developed and tested the similar active sampling pump, which was connected to an air bag on a hexacopter drone, to collect carbon dioxide, PM2.5 and PM10 above a corn field for examining.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Such laboratory analysis depends on the use of large canisters and sorbent cartridge devices, which must be carried by a large drone. Li et al (2020) also developed and tested the similar active sampling pump, which was connected to an air bag on a hexacopter drone, to collect carbon dioxide, PM2.5 and PM10 above a corn field for examining.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In [64], atmospheric particulate matter and carbon dioxide were measured using sUAS sampling and a bag collection system. The bags were collected and analyzed in a lab.…”
Section: Introductionmentioning
confidence: 99%
“…Several research studies have demonstrated the successful combination of UAVs and sensing technologies for visual inspection of buildings and construction conditions [13,14], outdoor air quality [15], and climatic research [16]. Different strategies have been applied, allowing sample collection for further laboratory analysis [16], or on-site sensing using detectors that allow data transfer to the operator. Particularly useful solutions allow high-resolution measurement, real-time data transfer, and spatiotemporal indexing.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these investigations presented sensors with a sampling inlet mounted under [22] or on [23] the UAV's hull. To diminish the propeller effect, extended stiff inlets, arranged above [16,24] or parallel [25] to the propeller plane, were also tested.…”
Section: Introductionmentioning
confidence: 99%